Effect of Beef Treatment at Different Temperatures on Myoglobin Changes : A Brief Review: Pengaruh Perlakuan Daging Sapi Pada Suhu Berbeda Terhadap Perubahan Mioglobin : Review Singkat - Izzah, Alya Nurul; Nurtiana, Winda; Ningrum, Marwah Astria; Anggraeni, Sherly; Nugroho, Insaan; Hasanah, As Shifa; Alfidah, Rahma; Febriyani, Rosa (Universitas Muhammadiyah Sidoarjo, 2024)
Myoglobin is the most important protein in the human and animal bodies, because myoglobin has a very important role in storing and transporting oxygen in muscle cells and giving meat its characteristic color. Each treatment used at different temperatures will have different changes. Meat storage treatments at different temperatures can have an effect on. The temperature methods used include room temperature, high temperature, low temperature and thawing. The color of the meat will change due to the interaction between myoglobin and oxygen which will form metmyoglobin after protein denaturation, so that it can change the color of the meat from reddish to brown and unattractive. When storing meat, it must be well controlled starting from air conditions and humidity so that it can maintain the red color of the meat. Apart from that, storage conditions and temperature control play an important role in storing meat, so that the quality of the meat lasts longer.